STUDIES ON THE INFLUENCE OF VESICULAR ARBUSCULAR MYCORRHIZA AND FERTILIZATION ON CHILI PEPPER (Capsicum annuum L.) IN DIFFERENT CROPPING SYSTEMS (2011)
Investigations were conducted with four pot and two field experiments on the influence of vesicular arbuscular mycorrhiza (VAM), and fertilization on chili pepper, Capsicum annuum var. tatase (Yoruba) in different cropping systems. All experiments were factorial in a randomized complete block design (RCBD) and each treatment was replicated three times. The first two pot experiments carried out in the Department of Botany and Microbiology, University of Ibadan under natural solar illumination and daily temperature, consisted of three types of VAM inoculation (Glomus mosseae, Glomus etunicatum and control), two levels of cropping systems (sole chili pepper and chili pepper intercropped with cowpea) and two levels of single superphosphate (0kg P/ha and 60kg P/ha) simultaneously in sterile and non-sterile soils. The third pot experiment consisted of three types of VAM inoculation (Glomus fasciculatum. Glomus mosseae and control), three levels of cropping systems (sole chili pepper, chili pepper with soybean intercrop and chili pepper with cowpea intercrop) and two levels of rock phosphate supplement (0kg P/ha and 60kg P/ha) in sterile. Finally the fourth pot experiment consisted of three species of VAM (Glomus mosseae, Glomus etunicatum and Glomus fasciculatum) three levels of organic fertilization (control, soybean intercrop and 5% organic manure) and three levels of rock P (0kg P/ha, 30kg P/ha and 60kg P/ha) also in sterile soil. The latter two pot experiments and the field experiments were located at National Horticultural Research Institute Ibadan, a derived savanna and transition zone between a tropical rain forest and southern guinea savanna. The first field experiment consisted of three types of VAM inoculation (Glomus mosseae, Glomus fasciculatum and control) three levels of cropping systems (sole chili pepper, chili pepper with cowpea intercrop and chili pepper with soya bean intercrop) and two levels of rock P (0kg P/ha and 60kg P/ha). The second field experiment consisted of three species of VAM fungi (Glomus mosseae, Glomus fasciculatum and Glomus etunicatum), three levels of organic fertilization (control, soya bean intercrop and 5% organic manure) and three levels of rock P (0kg P/ha, 30kg P/ha and 60kg P/ha). The soil pH (6.5) was significantly (P<0.05) reduced with Glomus mosseae inoculation while there was significantly (P<0.05) higher %C and Ca at 60kg P/ha than 0kg P/ha inorganic P supplement in non-sterile soil. Apart from P, the uptake of N, K, Ca, Mg, Zn and Fe were significantly (P<0.05) improved by mycorrhizal inoculation. The dry matter yield of mycorrhizal plant was significantly (P<0.05) higher than non-mycorrhizal plant with Glomus mosseae performing best in sterile soil. However, there was a significant drop (16%) in dry matter yield with the addition of 60kg P/ha single superphosphate. Mycorrhizal inoculated pepper plants had a twofold increase in fruit weight over uninoculated-mycorrhizal pepper plants. The use of rock P with organic manure in the presence of VAM enhanced fruit yield for chili pepper. There were significant (P<0.05) variations in the performance of mycorrhizal species in both pot and field experiments subject to soil environment and cropping systems. The experiment has provided the basis for the recognition of the fact that mycorrhizal activity is not only a component of plant system but also a soil-plant system improver.